2012
DOI: 10.1177/159101991201800303
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origins of Bilateral Vertebral Arteries in a Child with down Syndrome and Moyamoya Disease

Abstract: Variations in vertebral artery origin and course are well-described in the literature. The origin of right vertebral artery from the right common carotid artery is an extremely rare variant. We describe a unique case of a child with Down syndrome with variant origins of bilateral vertebral artery, an aberrant right subclavian artery and concomitant Moyamoya disease of intracranial circulation. The presence of variations of the origin and course of craniocervical arteries might have profound implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Prior studies have demonstrated a higher incidence of vascular anomalies in patients with Down syndrome; in fact, Rathore et al showed that the incidence of VA anomalies and aberrant RSCA in patients with Down syndrome is 40% and 36%, respectively [4,18- 19]. The case we report demonstrates both an aberrant RSCA and an anomalous origin of the right VA from the right CCA in a patient with Down syndrome.…”
Section: Discussionsupporting
confidence: 45%
“…Prior studies have demonstrated a higher incidence of vascular anomalies in patients with Down syndrome; in fact, Rathore et al showed that the incidence of VA anomalies and aberrant RSCA in patients with Down syndrome is 40% and 36%, respectively [4,18- 19]. The case we report demonstrates both an aberrant RSCA and an anomalous origin of the right VA from the right CCA in a patient with Down syndrome.…”
Section: Discussionsupporting
confidence: 45%
“…A potential etiological – pathogenetic link between the two entities or a common underlying chromosomal abnormality has been proposed 5. Mischra et al 6 reported a case with a very similar arterial disposition but without segmental absence of the VA and same clinical background, MMS with associated DS, that they named MM “disease” . In the current report, we preferred the term MMS based on the association with another medical condition (DS) 7.…”
Section: Discussionmentioning
confidence: 99%
“…During embryological development, the VA develops from the longitudinal anastomosis of the intersegmental arteries [ 11 , 12 ]. An abnormal development of the caudal portion of the intersegmental artery leads to the formation of a VA with an aortic origin which, in turn, may lead to an increased risk of developing VAH compared to a person with a normal VA [ 27 , 28 ]. In an autopsy study, the prevalence of VAs with an aortic origin was reported to be 2-6% [ 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%